EFEKTIFITAS PIJAT TUI NA DALAM MENGATASI KESULITAN MAKAN PADA BALITA DI RW 02 KELURAHAN WONOKROMO SURABAYA - Munjidah, Annif (Jurnal Ilmiah Kesehatan, 2015)
The Effectivity of Tui Na massage to overcome feeding difficulties in infants in RW 02 of Wonokromo District Surabaya. The children?s growth and development depends on the fulfillment of nutrients. Some problems which often occur in the fulfillment of nutrient are feeding difficulty in infants which can cause growth interference or stunting. The common cause of feeding difficulty in infants is divided into 3 factors, such as loss of appetite, impaired gastrointestinal function, and disruption of eating process of oral motor. To overcome feeding difficulty can be done through pharmacology or non pharmacology. The efforts of pharmacology way such as by giving miltivitamin, and another micronutrient. While non pharmacology way such as through drink herbal / herbs, massage, acupressure, and acupuncture. This study aims to analyze the effectivity of Tui Na massage in overcome feeding difficulty in infants. This was an observational analytic with crosssectional approach. The population used was all mothers and infants who are living in RW 02 Wonokromo District Surabaya as 27 people. The sample used is mostly mothers and the infants who were living in RW 02 of Wonokromo District Surabaya was 23 people. Its used a simple random sampling. The data were analyzed by Chi Square test with significant value alpha = 0.05. The results showed that the p value 0.009 < ? 0.05. Tui Na massage is effective to overcome feeding difficulty in infants in RW 02 Wonokromo District Surabaya. The conclusions of this study is the more routine Tui Na massage is done, the easier way to overcome feeding difficulty. It is expected that the infant?s mother are capable and routine to apply this massage